Rooming-in program in Dr. Sardjito Central General Hospital - Asparin Asparin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
To evaluate the clinical efficacy of rooming-in program, sixty one term-newborn infants with normal deliveries, birth weight 2500-4000 g, Apgar scores 5 minute were studied. The infants were randomly assigned into two groups, 31 rooming-in and 30 not rooming-in group (mother separated from the newborn for 3 days duration). In the third day of life, there were no statistically significant differences in both groups on serum bilirubin levels (p>0.05), cumulative weight loss (p>0.05) and incidence of hyperbilirubinemia (p>0.05). The intensity of hyperbilirubinemia was not related to weight loss (p>0.05). The episode of gastroenteritis was non-existent in the rooming-in group whereas two infants in the not rooming-in group suffered from it. Key Words: rooming-in program - term - newborn infants - unbound bilirubin - cumulative weight loss - hyperbilirubinemia